2007
DOI: 10.1152/ajpgi.00332.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enteric descending and afferent neural signaling stimulated by giant migrating contractions: essential contributing factors to visceral pain

Abstract: We investigated whether strong compression of an intestinal segment by giant migrating contractions (GMCs) initiates pseudoaffective signals from the gut, similar to those initiated by its distension with a balloon. The experiments were performed on conscious dogs by using close intra-arterial infusions of test substances that affect the receptors only in the infused segment. The stimulation of GMCs by close intra-arterial infusion of CGRP or distension of an intestinal segment by balloon increased the heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…19). Since active smooth muscle contraction is required for afferent nociceptive signaling and pseudoaffective response occurrence in response to CRD (33), the action on enteric neurons may have decreased the intensity of afferent discharge during CRD.…”
Section: Discussionmentioning
confidence: 99%
“…19). Since active smooth muscle contraction is required for afferent nociceptive signaling and pseudoaffective response occurrence in response to CRD (33), the action on enteric neurons may have decreased the intensity of afferent discharge during CRD.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain is a hallmark symptom of IBS, and feeding rodents probiotics or altering the gut microbiome with antibiotics [16][17][18][19][20] changes pseudoaffec-tive responses evoked by colorectal distension (CRD). Active smooth muscle contraction is necessary for nociceptive afferent signaling in response to CRD 21 and we have previously demonstrated that probiotics can affect the excitability of myenteric neurons, 22 thereby altering the intensity of propagated peristaltic contractions. Taken together, the data thus suggest that the change in excitability of myenteric neurons after exposure to certain bacterial species could be modulating the nociceptive response.…”
Section: Introductionmentioning
confidence: 99%
“…In daily life, strong compression of the colon wall by giant migrating contractions serves as the mechanical stimulus for evoked pain in these patients (10). The pain lasts nearly as long as balloon distension or as long as a giant migrating contraction is present anywhere in the colon (26). However, most diseases that cause peripheral nerve lesions also induce a feeling of ongoing pain/discomfort (neuropathic pain), as well as other aversive sensations, such as burning, numbness, tingling, and pricking, suggesting that peripheral nerve lesions may induce multiple types of affective feelings in addition to evoked pain (28).…”
mentioning
confidence: 99%